The Role of Gut Microbiota-derived Tryptophan Metabolites in Mycobacterium tuberculosis Infection: A Mini-Review - Novi Maulina; Zinatul Hayati; Kartini Hasballah; Zulkarnain Zulkarnain; Baidillah Zulkifli (The Faculty of Veterinary Medicine of Syiah Kuala University, 2022)
The gut microbiota has a major contribution in human physiology and influences disease pathogenesis, including in tuberculosis (TB) lung infection. Gut-lung axis has demonstrated the interplay of these two organs, mediated by metabolites produced by the gut microbes or derived from host molecules transformation. Tryptophan (Trp) is one of the essential aromatic amino acids catabolized as kynurenine, serotonin (5-hydroxytryptamine), and indole derivatives, including indole propionic acid (IPA), via 3 pathways. The latter was microbiota-derived Trp catabolism, which has known to have an immunomodulatory role, as ligands for Aryl hydrocarbon Receptor (AhR). Intriguingly, Mycobacterium tuberculosis required Trp as a nitrogen source, especially in CD4+ T cells-generated stress, to survive in the phagosome of macrophage and to cause disease. Recently, IPA is identified as a new anti-mycobacterial compound, which is specific and has broad spectrum of anti-mycobacterial activity. The structural similarity of this gut microbiota-derived metabolite and Trp allows IPA to inhibit the TrpE anthranilate synthase in Trp biosynthesis pathway in Mtb. In this review, we summarize findings from recent work by focusing on the role of Trp metabolites in host cells in TB infection. A better understanding of this chemical signal could potentially serve as a novel strategy for managing this chronic inflammatory disease.